Evaluation of a screening test for detecting urinary tract infection in newborns and infants. Issue 12 (December 1991) - Lejeune, B; Baron, R; Guillois, B; Mayeux, D
Abstract : The results of a study of a screening test for urinary tract infection (UTI) in infants under 18 months is reported. Two hundred and forty three urine specimens were tested in the laboratory using AMES Multistix 8SG reagent strips read by photometer. The strips included three potential markers for urinary tract infection: leucocyte esterase, nitrite, and protein. The predictive value of a positive result (PPV) was low. The predictive value of negative test (NPV) when combining the screen of leucocyte esterase, nitrite, and protein was 99.4% with no difference between boys and girls. The test for leucocyte esterase had a 97.6% negative predictive value. An examination of the results by age confirms the good NPV in all age groups. Paediatricians should find Multistix 8SG strips a useful aid in the diagnosis of urinary tract infection in infants, and that costly culture of samples with negative strip tests can be avoided.